WELCH, Clifford A. et all (Orgs.). Camponeses brasileiros. Vol. 1: Leituras e interpretações clássicas. São Paulo: Ed. da UNESP: Ministério do Desenvolvimento Agrário, NEAD, 2009. 336p. (Dialogos, 2017)
Resenha.